FlexRay and its Applications : Real Time Multiplexed Network. - Paret, Dominique (John Wiley & Sons, 2012)
An authoritative yet highly accessible guide to the design and operation of the FlexRay bus, the latest protocol for automotive network communicationsA translation of the French edition, originally published in January 2011, this work is the result of numerous training courses that Dominique Paret has given in companies, and it provides detailed explanations of the design and operation of the FlexRay bus. Comprised of five parts the book covers: the FlexRay concept and its communication protocol; the FlexRay physical layer; synchronization and global time and; architecture of a node, component.